Impact of diet composition and temperature–humidity index on water and dry matter intake of high‐yielding dairy cows. Issue 1 (15th March 2017) - Ammer, S.; Lambertz, C.; von Soosten, D.; Zimmer, K.; Meyer, U.; Dänicke, S.; Gauly, M.
Summary: The temperature–humidity index (THI) is widely used to characterize heat stress in dairy cattle. Diet composition is known to induce variation in metabolic‐associated heat production. However, the relationships between THI and diet are poorly characterized with regard to performance and intake behaviour. Therefore, the objectives were to evaluate the impact of THI on water intake (WI), dry matter intake (DMI) and the frequency of drinking and feeding bouts in lactating dairy cows offered four dietary treatments: each contained 20% grass silage and additionally (i) 20% maize silage, 60% concentrate (M‐HC); (ii) 60% maize silage, 20% concentrate (M‐LC); (iii) 20% pressed beet pulp silage, 60% concentrate (BPS‐HC); or (iv) 60% pressed beet pulp silage, 20% concentrate (BPS‐LC) (DM basis). Individual WI and DMI were recorded from April to July 2013. Furthermore, dietary effects on milk production and reticular pH were estimated. Milk yield was lowest for M‐LC, while energy‐corrected milk was similar for all diets. Milk fat percentage was higher and milk protein amount lower for cows offered both LC diets. Reticular pH below 6.3, 6.0 and 5.8 lasted longest for BPS‐LC. WI was higher for HC diets. However, the frequency of drinking bouts was not influenced by the ration. Lower DMI occurred for BPS‐LC compared to M‐LC. Frequency of feeding bouts was significantly higher for LC diets. THI was significantly related to WI, DMI as well as drinking and feeding bouts. Per increasing THI, WI increased slightly more for LC diets and DMI decreased more for HC diets. Frequency of drinking bouts increased slightly higher for BPS rations per rising THI, while the decrease in feeding bouts was highest for M‐HC. In conclusion, TMR composition and moderate heat stress impacted WI and DMI of dairy cows, while both dietary energy density and ruminal filling might intensify the THI impact.